Mineral potential modelling of gold and silver mineralization in the Nevada Great Basin: A GIS-based analysis using weights of evidence. - Mihalasky, Mark John. (University of Ottawa (Canada), 1998)
The distribution of 2,690 gold-silver-bearing occurrences in the Nevada Great Basin was examined in terms of spatial association with various geological phenomena. Analysis of these relationships, using GIS and weights of evidence modelling techniques, has predicted areas of high potential where little or no mining activity exists. Mineral potential maps for sedimentary ("disseminated") and volcanic ("epithermal") rock-hosted gold-silver mineralization revealed two distinct patterns that highlight two sets of crustal-scale geologic features that likely control the regional distribution of these deposit types. Mineral potential maps predicting the distribution of gold-silver-bearing occurrences successfully predicted nearly 70% of the total number of known occurrences. In blind tests, the sedimentary and volcanic rock-hosted mineral potential maps predicted 10 out of 12 and 5 out of 5 occurrences, respectively. The key mineral predictor factors, in order of importance, were determined to be: geology (including lithology, structure, and lithotectonic terrane), geochemistry (indication alteration), and geophysics. Areas of elevated sedimentary rock-hosted mineral potential are generally confined to central, north-central, and north-eastern Nevada. These areas form a conspicuous "V"-shape pattern that is coincident with the Battle Mountain-Eureka (Cortez) and Carlin mineral trends and a segment of the Roberts Mountain thrust front, which bridges the southern ends of the trends. This pattern appears to delineate northwest-southeast-trending crustal-scale structural zones, here termed the "Carlin" and "Cortez" structural zones. Mineralizing processes were focused along these structural zones. The Carlin and Cortez structural zones are considered to be transcurrent features representing a long-lived, deep-crustal or mantle-rooted zone of weakness. Areas of elevated volcanic rock-hosted mineral potential are principally distributed along two broad and diffuse belts that trend (1) northwest-southeast across Nevada, parallel to the Sierra Nevada, and (2) northeast-southwest across northern Nevada, extending diagonally from the Sierra Nevada to southern Idaho. The first belt corresponds to the Walker Lane shear zone, a wide region of complex strike-slip faulting. The second, here termed the " Humboldt shear(?) zone", may represent a structural zone of transcurrent movement. Volcanic rock-hosted mineralizing was closely tied to the southward and westward migration of Tertiary magmatism across the region (which may have been mantle plume-driven). Latest movement along the Humboldt shear(?) zone is constrained between ∼42-30 Ma (sedimentary rock-hosted mineralization) and ∼17-14 Ma, (most recent igneous activity along the northern Nevada rift zone). (Abstract shortened by UMI.)
Keywords: Physical Geography.